Implementation challenges in delivering team-based care ('TEAMcare') for patients with chronic obstructive pulmonary disease in a public hospital setting: a mixed methods approach. Issue 1 (December 2016) - Cochrane, Belinda; Foster, Jann; Boyd, Robert; Atlantis, Evan
Abstract Background Chronic obstructive pulmonary disease (COPD) is considered a multisystem disease, in which comorbidities feature prominently. COPD guidelines recommend holistic assessment and management of relevant comorbid diseases but there is limited information as to how this is best achieved. This pilot study aimed to explore the views of stakeholders, including patients and the healthcare team, on the feasibility, acceptability and barriers to a collaborative, multidisciplinary team-based care intervention ('TEAMcare') to improve health outcomes in COPD patients, within the context of a local hospital outpatient clinic. Methods A mixed methods study design was used. A COPD care algorithm was developed based on the Australasian guidelines, COPDX. COPD participants were consecutively recruited from an outer metropolitan hospital's respiratory clinic. Participants attended for follow up visits at 5 and 10 months to ascertain clinical status, algorithm compliance and to review and revise management recommendations. The intervention was conducted using existing resources, involving collaboration with general practice and the publicly-funded local chronic disease management programme (Medicare Local). Stakeholders provided qualitative feedback about the intervention in terms of feasibility, acceptability and barriers via structured and semi-structured interviews. All interviews were recorded, transcribed verbatim and analysed using qualitative thematic analysis to identify key concepts and themes. Results The study protocol was abandoned prematurely due to clear lack of feasibility. Of 12 participants, 4 withdrew and none completed pulmonary rehabilitation (PR). The main reasons for non-participation or study withdrawal related to reluctance to attend PR (6 of 16) and the burden of increased appointments (4 of 16). PR conflicted with employment hours, which presented problems for some participants. Similarly, themes that emerged from qualitative data indicate healthcare provider perception of deficiencies in funding (for infrastructure and staffing). Health literacy, motivation, organisation and functional impairment were issues for patients. Conclusions Available data from this small pilot provided valuable insights to inform future design and implementation strategies. Delivering structured team-based care to COPD patients presents challenges. In addition to enhancing health resources for engaging COPD patients, a focus on health literacy and improving health service access, including colocalisation and access outside business hours, may be required. Trial Registration ACTRN12616000342415 ; 16/03/2016.